Identification of chemical compounds in liquid aroma for swiftlet ranching - Ong, Foo Kheng (2012)
Bird's nest is an excellent restorative food with a sweet and calm character; it is good for any age or gender. Therefore bird's nest is highly popular among the Chinese communities. This make swiflets ranching industry is growing stronger and stronger in our nation. The major swiftlet ranching areas are located mostly in secondary and tertiary townships where food source is in abundance and pollution levels are at their relative minimum. Bird's nest is actually dried saliva of swiftlet, therefore in swiftiet farming; owners tend to have various kinds of way to attract swiftiet to their bird house. However some birdhouse owners complained that they are not getting the desired result that very few swiftiets are staying in their house to build their nests. Basically it is affected by a few parameter which is sound, design of bird house, location and also aroma attraction. Therefore the objective of the study is to analysis chemical compounds in aroma using solid phase microextraction (SPME) with coupled with gas chromatography-mass spectroscopy (GC-MS). By using all these powerful analytical instrument, able to detect compound that present in liquid aroma that use to attract swifilet to build nest in the bird house. For volatile chemical compounds, SPME which coupled with GC-MS is used. Therefore by using these method, able to identify chemical compounds to attract bird swiftlet to bird house.